2013
DOI: 10.1371/journal.pone.0065555
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retinal Morphology, Electroretinogram and Visual Behavior after Transient Global Ischemia in Adult Rats

Abstract: The retina is a light-sensitive tissue of the central nervous system that is vulnerable to ischemia. The pathological mechanism underlying retinal ischemic injury is not fully understood. The purpose of this study was to investigate structural and functional changes of different types of rat retinal neurons and visual behavior following transient global ischemia. Retinal ischemia was induced using a 4-vessel occlusion model. Compared with the normal group, the number of βIII-tubulin positive retinal ganglion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 52 publications
2
31
3
Order By: Relevance
“…If the nutrient supply (i.e., circulation) is restored within this time window of 1 hour, one can assume that the prospects for a restoration of visual function are still quite high. The retinal tolerance to short ischemic durations has also been shown by Zhao et al 16 in rat eye. There, the retinal arteries were occluded for 17 minutes, followed by reperfusion.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…If the nutrient supply (i.e., circulation) is restored within this time window of 1 hour, one can assume that the prospects for a restoration of visual function are still quite high. The retinal tolerance to short ischemic durations has also been shown by Zhao et al 16 in rat eye. There, the retinal arteries were occluded for 17 minutes, followed by reperfusion.…”
Section: Discussionsupporting
confidence: 52%
“…4 These results prompted us to investigate the influence of hypothermia systematically. This question has been addressed by several studies in rodents, [14][15][16] but investigations with an animal model system closer to the human are still missing. Here we used retinas of minipigs to investigate the time course of retinal damage and the protective potential of hypothermia, and we compared these results with data from postmortem iovs.arvojournals.org j ISSN: 1552-5783 human retina.…”
mentioning
confidence: 99%
“…The elevated IOP was associated with markedly enhanced pSTR amplitudes compared to baseline values in both anaesthetic groups. These data, at first, appear to be contradictory to other experiments involving STRs and IOP changes, which tend to show decreases in STR amplitudes[13,22,25]. However, the STRs in the present study were recorded within a relatively short time, less than an hour of elevated IOP, and represent an acute stress response, rather than a delayed and/or chronic stress response associated with cell death [17,25,39].…”
Section: Discussioncontrasting
confidence: 99%
“…The IOP elevation was maintained at 33–40 mmHg in our experiments, whereas some previous studies included IOP levels that were higher and were therefore ischaemic [14,19,22,43,44]. We also have reported that using the loop at ischaemic IOP levels (80 mmHg) abolishes STRs [16].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation